Wartość macierzyństwa jako wymiar poczucia szczęścia bezdomnych kobiet - Piechowicz-Bogaczyk, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
This article is an attempt to describe and analyse the value of motherhood as a dimension of the sense of happiness reported by women experiencing homelessness. The research relies on case study methodology. Analysed is empirical material from five narrative interviews. The text has a numer of structural components. The first two are introductory as they cover the theoretical foundations of the research (the concept of homelessness of women and the concept of motherhood). These are followed by methodological assumptions. The fourth part presents research results, while the final part contains an analysis and discussion with reference to previous relevant research reports. The article ends with a handful of practical conclusions.